Nano-Perforated Silicon Membrane with Monolithically Integrated Buried Cavity - Sanjeev Vishal Kota; Anil Thilsted; Daniel Trimarco; Jesper Yue Pan; Ole Hansen; Jörg Hübner; Rafael Taboryski; Henri Jansen (Micromachines)
A wafer-scale process for fabricating monolithically suspended nano-perforated membranes (NPMs) with integrated support structures into silicon is developed. Existing fabrication methods are suitable for many desired geometries, but face challenges related to mechanical robustness and fabrication complexity. We demonstrate a process that utilizes the cyclic deposit, remove, etch, and multi-step (DREM) process for directional etching of high-aspect-ratio (HAR) 300 nm in diameter nano-pores of 700 nm pitch. Subsequently, a buried cavity beneath the nano-pores is formed by switching to an isotropic etch, which effectively yields a thick NPM. Due to this architecture’s flexibility and process robustness, structural parameters such as membrane thickness, diameter, integrated support structures, and cavity height can be adjusted, allowing a wide range of NPM geometries. This work presents NPMs with final thicknesses of 4.5 µm, 6.5 µm, and 12 µm. Detailed steps of this new approach are discussed, including the etching of a through-silicon-via to establish the connection of the NPM to the macro-world. Our approach to fabricating NPMs within single-crystal silicon overcomes some of the limitations of previous methods. Owing to its monolithic design, this NPM architecture permits further enhancements through material deposition, pore size reduction, and surface functionalization, broadening its application potential for corrosive environments, purification and separation processes, and numerous other advanced applications.